1990
DOI: 10.1029/ja095ia05p06209
|View full text |Cite
|
Sign up to set email alerts
|

Currents between tethered electrodes in a magnetized laboratory plasma

Abstract: Laboratory experiments on important plasma physics issues of electrodynamic tethers are performed. These include'cunent propagation, formation of wave wings, limits of current collection, nonlinear effects and instabilities, charging phenomena, and characteristics of transmission lines in plasmas. The experiments are conducted in a large afterglow plasma (100 cm x 200 cm, ne -< 1012 C m-3, kT,, _< 3 eV, Bo < 100 G, Ar, Pn --3 x 10 -4 Torr). The current system is established with a small electron-emitting hot c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 40 publications
2
22
1
Order By: Relevance
“…Basing on the characteristics of the observed instability, it has been assumed that the instability is stimulated by the energetic ion component produced during the resonant absorption of the microwave. It has been shown that this instability differs from the previously reported processes 2,6-10, 12,13,17,18,21 and is characterized by the following features: ͑i͒ oscillations in the probe current occur only when the probe is biased positively with respect to the plasma potential, ͑ii͒ the instability is driven by a flux of suprathermal ions entering the sheath area of the probe, and ͑iii͒ the instability amplitude exhibits saturation, when the energetic ion component is reflected inside the sheath and cannot reach the probe surface.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Basing on the characteristics of the observed instability, it has been assumed that the instability is stimulated by the energetic ion component produced during the resonant absorption of the microwave. It has been shown that this instability differs from the previously reported processes 2,6-10, 12,13,17,18,21 and is characterized by the following features: ͑i͒ oscillations in the probe current occur only when the probe is biased positively with respect to the plasma potential, ͑ii͒ the instability is driven by a flux of suprathermal ions entering the sheath area of the probe, and ͑iii͒ the instability amplitude exhibits saturation, when the energetic ion component is reflected inside the sheath and cannot reach the probe surface.…”
Section: Introductioncontrasting
confidence: 61%
“…[6][7][8][9][10] This deep interest to sheath processes is stimulated mainly by their great importance for every device used in fundamental and applied plasma studies, such as plasma diagnostic techniques, [11][12][13][14] plasma diodes 15 and discharges, 2,9,[16][17][18] antennas in plasmas, 6,7,13,19 current systems in space, [20][21][22][23] and satellite charging processes. [23][24][25] High-frequency sheath-plasma processes, which occur in the vicinity of the local plasma frequency, have been widely studied in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Stenzel et al investigated the plasma dynamics of positive probes (r p < r i ) in MDP in a pulsed non-drifting plasma apparatus. [9][10][11] By using the principle of superposition, they extrapolated their observation of a whistler pulse excited when a bias was applied between a positive probe and an electron emitter to MDP conditions and predicted whistler wings could be excited by positive probes in MDP. In three dimensional electrostatic particle-in-cell (PIC) simulations, Singh et al simulated positive probes (r p < r i ) in MDP and made observations of anomalous current collection, wing-like potential structures, and lower hybrid waves in the ion ram region that they identified as a free energy source for electron heating.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that there is no whistler emission (part W on the FM branch of Figure 1); Stenzel and Urrutia's experiments showing whistlers do not apply to an ionospheric tether; they either fail to reproduce the steady condition u> = k x V [Vrrutia and Stenzel, 1989] or correspond to the opposite regime V ~ 2 x 10 7 cm/s>-K A -4x 10 5 cm/s [Stenzel and Urrutia, 1990]. Radiation occurs at the contactors, where V • j s / 0, because it depends on the source divergence kj £ , a fact first noticed by Esies [1988] and clearly arising from the quasi-electrostatic character of the field, E~ -iki/j or -tkj_<#.…”
Section: Wave Emissionmentioning
confidence: 99%